2022
DOI: 10.3390/ijms23042178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Fertilizer on Quality Characteristics of Wheat with the Absence of Different Individual High-Molecular-Weight Glutenin Subunits (HMW-GSs)

Abstract: High-molecular-weight glutenin subunits (HMW-GSs) are important components of gluten, which determine the grain quality of wheat. In this study, we investigated the effects of nitrogen (N) fertilizer application on the synthesis and accumulation of grain protein and gluten quality in wheat lines with different HMW-GSs absent. The results showed that the absence of the HMW-GS in the wheat variety Ningmai 9 significantly decreased the contents of gluten, glutenin macropolymer (GMP), protein compositions, HMW-GS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…In agreement with these reports, we observed increased GPC and wet gluten content, a higher Gli/Glu ratio, and a negative correlation between DST and the Gli/Glu ratio in response to higher N rates. Here, a large discrepancy was found between our result and those of Yang et al and Zheng et al, who found that the protein quality index increased as the N application rate increased from 0 kg to an optimum rate under different experiment conditions. In our experiment, the DST and R max decreased when the N rate increased from 100 to 200 kg ha –1 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In agreement with these reports, we observed increased GPC and wet gluten content, a higher Gli/Glu ratio, and a negative correlation between DST and the Gli/Glu ratio in response to higher N rates. Here, a large discrepancy was found between our result and those of Yang et al and Zheng et al, who found that the protein quality index increased as the N application rate increased from 0 kg to an optimum rate under different experiment conditions. In our experiment, the DST and R max decreased when the N rate increased from 100 to 200 kg ha –1 .…”
Section: Discussioncontrasting
confidence: 99%
“…Some of these differences may be related mainly to the genotypes and the N availability in the soil. We studied GY5766, which is a bread wheat cultivar, whereas Yang et al . and Zheng et al studied soft wheat cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Ningmai 9 is a soft wheat variety with wide adaptability and stable yield in middle and lower reaches of the Yangtze River. Our previous study showed that the deletion of HMW-GS in Ningmai 9 had a close yield as wild type under different nitrogen fertilizer regulation levels . Besides, we also found that the deletion of individual HMW-GS in Ningmai 9 changed physicochemical properties of starch and improved the biscuit processing quality .…”
Section: Introductionmentioning
confidence: 61%
“…Our previous study showed that the deletion of HMW-GS in Ningmai 9 had a close yield as wild type under different nitrogen fertilizer regulation levels. 16 Besides, we also found that the deletion of individual HMW-GS in Ningmai 9 changed physicochemical properties of starch and improved the biscuit processing quality. 17 Though previous research studies had also reported the relationship between gluten strength and HMW-GS deletion, 18,19 the molecular mechanism behind the gluten and dough property changes triggered by HMW-GS deletion still remained unclear and required further investigation.…”
Section: ■ Introductionmentioning
confidence: 65%
“…Gluten is composed of glutenins and gliadins. Glutenins consist of high‐molecular‐weight (HMW) and low‐molecular‐weight (LMW) glutenin subunits (GSs), which form gluten polymers through intermolecular bisulfide bonds that influence dough elasticity (Ma et al ., 2019; Yang et al ., 2022). Gliadins are traditionally divided into α/β‐, γ‐, ω‐, and δ‐gliadins based on differences in their primary structure; through their interaction with glutenins, gliadins contribute to dough viscosity (Wang et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%